ANALYSIS OF FC'30 MPA FAST TRACK CONCRETE WITH THE ADDITION OF DRAMIX STEEL FIBER AND POLYETHYLENE TEREFTLATE (PET) AS AGGREGATE COARSE SUBSTITUTION FOR ROAD CLASS III - Najib, Muhammad; Mudiyono, Rachmat; Sulistyo, Juny Andri (Pondasi, 2024)
Fast track concrete is a ready-mix concrete that hardens quickly and can be used directly for traffic. This concrete has special specifications that cover the needs of road pavement segment concrete that is opened for traffic when the concrete age is less than 7 days. This study aims to determine the value of compressive strength and flexural strength of concrete with a comparison of substitution of dramix steel fiber and Polyethylene Terephlate (PET) aggregate. This study uses an experimental method with a trial of testing concrete cylinders and beams with compressive and flexural tests with four compositions of normal concrete, dramix steel fiber substitution concrete, Polyethylene Terephlate (PET) aggregate substitution concrete and concrete with a combination of dramix steel fiber and Polyethylene Terephlate (PET). The composition test was carried out on fast track concrete with a quality of fc'30 Mpa within 4 days including compressive strength and flexural strength when the test object was 4, 7, 14, 21 and 28 days old. The results of the study showed that the use of dramix substitution concrete had the best results with an average compressive strength value of 30 Mpa fast track concrete within 4 days of 29.92 Mpa and a flexural strength of 3.59 Mpa greater than the mixture of substitution concrete Polyethylene Terephlate (PET) aggregate substitution obtained an average compressive strength of 20.785 and flexural strength of 3.35 in a concrete age of 4 days and the combination of dramix substitution and Polyethylene Terephlate (PET) aggregate concrete had an average compressive strength value of 21.31 Mpa and Flexural strength of 3.41 Mpa at the age of 4 days, which later the value will continue to increase until the immersion age of 28 days.